The Effect of Tax Planning, Deferred Tax Expense, and Taxpayer Compliance on Earnings Management in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) for the 2019–2023 Period - Nadia Novianti; Danang Choirul Umam (SEAN Institute, 2026)
This study aims to examine the influence of tax planning and deferred tax expense on earnings management in food and beverage companies listed on the Indonesia Stock Exchange. The research is grounded in agency theory and positive accounting theory, which explain managerial incentives in financial reporting decisions. A quantitative approach with an associative design is employed to analyze the relationship between the variables. The data used in this study are secondary data obtained from published financial statements of companies within the selected sector. The sampling technique applied is purposive sampling based on specific criteria to ensure data completeness and consistency. The findings indicate that tax planning has a positive and significant effect on earnings management, suggesting that more effective tax strategies provide greater flexibility for managers to adjust reported earnings. In contrast, deferred tax expense shows a negative and significant effect, implying that it acts as a constraint on managerial discretion in earnings manipulation. These results highlight the dual role of tax-related variables as both enabling and limiting factors in earnings management practices. This study contributes to the literature by providing empirical evidence on the relationship between taxation strategies and financial reporting behavior within a specific industrial context. The findings also offer practical implications for stakeholders to critically evaluate tax-related information as potential indicators of earnings management.